Inhibitory effect of purple rice husk extract on AFB1-induced micronucleus formation in rat liver through modulation of xenobiotic metabolizing enzymes - Arpamas Chariyakornkul (2019)
© 2019 The Author(s). Background: Rice husk, a waste material produced during milling, contains numerous phytochemicals that may be sources of cancer chemopreventive agents. Various biological activities of white and colored rice husk have been reported. However, there are few comparative studies of the cancer chemopreventive effects of white and colored rice husk. Methods: This study investigated the cancer chemopreventive activities of two different colors of rice husk using in vitro and in vivo models. A bacterial mutation assay using Salmonella typhimurium strains TA98 and TA100 was performed; enzyme induction activity in murine hepatoma cells was measured, and a liver micronucleus test was performed in male Wistar rats. Results: The white rice husk (WRHE) and purple rice husk (PRHE) extracts were not mutagenic in Salmonella typhimurium TA98 or TA100 in the presence or absence of metabolic activation. However, the extracts exhibited antimutagenicity against aflatoxin B1 (AFB1) and 2-amino-3,4 dimethylimidazo[4,5-f]quinolone (MeIQ) in a Salmonella mutation assay. The extracts also induced anticarcinogenic enzyme activity in a murine Hepa1c1c7 hepatoma cell line. Interestingly, PRHE but not WRHE exhibited antigenotoxicity in the rat liver micronucleus test. PRHE significantly decreased the number of micronucleated hepatocytes in AFB1-initiated rats. PRHE contained higher amounts of phenolic compounds and vitamin E than WRHE in both tocopherols and tocotrienols as well as polyphenol such as cyanidin-3-glucoside, protocatechuic acid and vanillic acid. Furthermore, PRHE increased CYP1A1 and 1A2 activities while decreasing CYP3A2 activity in the livers of AFB1-treated rats. PRHE also enhanced various detoxifying enzyme activities, including glutathione S-transferase, NAD(P)H quinone oxidoreductase and heme oxygenase. Conclusions: PRHE showed potent cancer chemopreventive activity in a rat liver micronucleus assay through modulation of phase I and II xenobiotic metabolizing enzymes involved in AFB1 metabolism. Vitamin E and phenolic compounds may be candidate antimutagens in purple rice husk.